Por palavras e ações: há um mundo entre nós. Justiça, liberdade e comunhão: sentidos teológicos e políticos nos paradoxos da democracia em tempos de direitos humanos - Oliveira, Kathlen Luana de (2013)
The understanding of the traces of the movement of meanings in speeches on justice, freedom and communion/community from situations and places in contemporary Brazilian context, given the varied forms of violence, asks for the possibilities of being-together, of novelty. Like a woof, we analyze the semantic disputes that cross the claims from human rights, the theological thinking and that are associated with democratic achievements. Arendt s thinking and theological reflections gestated in the postcolonial and freedom context are the main theoretical framework, presented in the introduction, along with methodological aspects. In the first chapter, the meanings of justice are analyzed from the experiences of injustice, in places of denial of inhabiting the city, denial for the memory of missing political people and of sociability that, by fear and distrust of public institutions, accomplishes justice by lynching. Before the importance of memory, biographies and the inhabiting in the city, we analyze the possibilities of factual truth, of witnessed truth, and the possibilities of forgiveness as protesters of the limits of the meanings of justice. In the second chapter, the meanings of freedom are investigated from the experiences of conflicts arising from the PNDH-3 [National Plan of Human Rights-3], the struggle of women against the criminalization of abortion, conflicts on religious freedom, for the freedom of inhabiting in the countryside and in the city; conflicts of freedom of expression and the right to memory. Due to the meanings built in proximity and distinction, we present speeches on freedom and liberation, specifically, in the path of liberation theologies. In dialogue, Arendt s perspective is presented as a disruptive of the idea of sovereignty, and as possibilities of freedom of being-together, in an event of miracle. In the third chapter, communion/community is discussed from the speeches of distrust and discredit of institutionalities and representations questioning the sacredness of belonging and the notion of sovereignty that underlie/justify violence. The understanding of being-together is investigated as contrasting stipulated consensus, social cohesion, the idea of absolute theological or foundational community. Therefore, inhabiting the world, being-together, is understood in parallel with diaspora , exile , aiming at the unveiling of perceptions of identities and absolute communities, indicating the plurality of its own constitution. Starting from the exposed presence, in appearance, in meeting that do not deny the quarrelsome, the meaning of tupinambá anthropophagy is added, showing the importance of obscene, of laughing, involving a reciprocal transformation in being-together. The tupinambá anthropophagy, as a way of thinking on being-together, on community/communion, aims propositions of deconstructing the ideas of absolute identities and communitarianism, in possibilities of relations that creates and recreates themselves. The conclusion points to a theology that fulfills itself through political options, for the unglorification of violence, for the desacralization of institutions, for the critic to natural belongings, the communitarian and individual absolutism, questioning the notion of sovereignty and privatization, indicating possibilities of forgiveness, of action, of being-together in the horizon of miracle, as an event of new relationships.